TUC Equal Pay Resolution, 1888 (1888)
1888 1880-1914 "TUC Equal Pay Resolution, 1888" [EP0051a], 1888 In 1888, Clementina Black moved the first TUC equal pay resolution. This report comes from the 15 September, 1888 issue of The Women's Union Journal published by the Women's Trade Union League.